Vulnerability and Adaptation to Drought The Canadian Prairies and South America - Warren, Jim; Diaz, Harry; Hurlbert, Margot (University of Calgary Press, 2016)
Although there is considerable historical literature describing the social and economic impact of drought on the prairies in the 1930s, little has been written about the challenges presented by drought in more contemporary times. The drought of 2001-02 was, for example, the most recent large-area, intense, and prolonged drought in Canada and one of Canada's most costly natural disasters in a century. Vulnerability and Adaptation to Drought describes the impacts of droughts and the adaptations made in prairie agriculture over recent decades. These adaptations have enhanced the capacity of rural communities to withstand drought. However, despite the high levels of technical adaptation that have occurred, and the existing human capital and vibrant social and information networks, agricultural producers in the prairie region remain vulnerable to severe droughts that last more than a couple of years. Research findings and projections suggest that droughts could become more frequent, more severe, and of longer duration in the region over the course of the 21st century. This book provides insights into the conditions generating these challenges and the measures required to reduce vulnerability of prairie communities to them. Developing greater understanding of the social forces and conditions that have contributed to enhanced resilience, as well as those which detract from successful adaptation, is a principal theme of the book. To that end, the book examines drought through an interdisciplinary lens encompassing climate science and the social sciences. Two of the chapters are based on the drought experiences of other countries in order to provide a comparative assessment.